Energy Balances and Electricity Profiles 2010 - United Nations (United Nations, 2013)
The 2010 Energy Balances and Electricity Profiles contains energy balances for about 115 developing countries, showing production, trade, conversion and consumption in energy units for all energy products; and electricity profiles for about 190 countries, providing detailed information on production, trade and consumption of electricity, net installed capacity and thermal power plant input for selected developing and developed countries.